Relationship Between Principals’ Human Skills and Job Satisfaction of Secondary School Teachers with Mediating role of School Climate - Faheem Khan; Muhammad Junaid Siraji; Qamar uz Zaman; Zafrullah Khan Khattak; Qaisar Anwar; Asif Minhas (Journal of Social Sciences and Management Studies, 2022)
The current study was aimed to investigate the relationship between principals’ human skills and job satisfaction of secondary school teachers with mediating role of school climate. A sample of 271 Secondary School Teachers (SSTs) was selected through stratified sampling method. A questionnaire was developed for data collection purpose. Pearson-Product Correlation and mediation analysis was used. The results of the study indicated that school climate partially mediated in the relationship between principals’ human skills and teacher’ job satisfaction. The study recommended that school principals may emphasis and develop their human skills.